Pengoptimalisasi Sistem Distribusi Pesanan Buku Paket dengan Metode DRP & Tabu Search - Firman Aldiansyah; Asep Endih Nurhidayat (Jurnal Indonesia Sosial Sains, 2022)
When the company purchases goods, the goods storage process is carried out using certain administrative records to implement planning and control to prevent shortages and excess inventories as well as acts of fraud that harm the company. The methods used in collecting research data are the Distribution Requirement Planning (DRP) and Tabu Search methods. . The data in this study were obtained based on recap data on the distribution of goods carried out by CV Almira Jaya Abadi. The purpose of this research is to plan distribution to focus more on product demand and delivery scheduling plans at CV Almira Jaya Abadi. Planning product orders using the DRP method. Comparing the total costs incurred with the company's method. Knowing the product distribution process system applied in this company. After forecasting, testing the DRP method for planning distribution schedules in the 2021 period. distribution using the DRP method found that after forecasting, the distribution cost of the DRP method during the 2021 period was Rp. 214,985. Comparison of the calculation of distribution costs between the company's method and the DRP method before forecasting, the results show that the DRP method is more profitable with a product distribution cost of IDR 2,085,015 compared to the company's initial cost of IDR 2,300,000. The company achieves efficiency through distribution calculations using the Distribution Requirement method. Planning according to the calculation on the first point is 90.65%.